2016
DOI: 10.1021/acssynbio.6b00170
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand-Displacement Timer Circuits

Abstract: Chemical circuits can coordinate elaborate sequences of events in cells and tissues, from the self-assembly of biological complexes to the sequence of embryonic development. However, autonomously directing the timing of events in synthetic systems using chemical signals remains challenging. Here we demonstrate that a simple synthetic DNA strand-displacement circuit can release target sequences of DNA into solution at a constant rate after a tunable delay that can range from hours to days. The rates of DNA rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 32 publications
0
65
0
Order By: Relevance
“…55 for more details). The bands corresponding to the complexes were identied using UV-shadowing at a wavelength of 254 nm.…”
Section: Dna Complex Preparationmentioning
confidence: 99%
“…55 for more details). The bands corresponding to the complexes were identied using UV-shadowing at a wavelength of 254 nm.…”
Section: Dna Complex Preparationmentioning
confidence: 99%
“…Systems of synthetic oligonucleotides have been successfully designed as switches, amplifiers, logic gates, and oscillators. [24][25][26][27] By programming these circuits to produce specific TF sequences as outputs, they can function as embedded controllers for programming gene-expression dynamics under our framework. This use of nucleic-acid computing for the active, on-demand synthesis of functional RNAs could find applications in biological analysis, directed evolution, and molecular information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Analog computing with transients Recognizing temporal patterns can be interpreted as an analog operation that is naturally suited for molecular computation. While molecular circuits of digital gates have solved remarkable problems [12][13][14] and even mimicked deep neural networks [15], several recent papers [16][17][18][19][20][21][22][23][24][25] have shown that analog computations are naturally suited for molecular circuits. Analog operations represent information directly in continuous physical variables like concentration or time intervals [26,27].…”
mentioning
confidence: 99%